Hubungan Antara Supervisi Kepala Sekolah dan Kompetensi Pedagogik Guru Madrasah Ibtidaiyah Se-Kota Lhokseumawe - Nurmayuli, Nurmayuli (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2019)
The purpose of this study is to determine the supervisory relationship between Principals and pedagogical competencies of Lhokseumawe City Madrasah Ibtidaiyah Teachers. This research is a quantitative study carried out in 9 Islamic Madrasas throughout the city of Lhokseumawe. The number of population are 245 teachers and the sample are 71 teachers. Sampling using the proportionete stratified random sampling technique, the data analysis technique tests the hypothesis using simple regression analysis and correlation analysis, while as a simple regression prerequisite test using the classical assumption test (normality test, reliability test, heteroscedasticity test, and linearity test). The results of this research are the supervision of the principal has an influence on the pedagogical competence of the teacher with the regression equation (Competence = 90,329 + 0,159 supervision) means that each addition of 1% the variable value of supervision then the value of pedagogical competency variable increases by 0,159, with the correlational value in sufficient category that is 0,411 , then the magnitude of the influence of the principal's supervision factor on teacher pedagogical competencies is 0.169 or 16.9%